Extraction of energy-dense components of the combustible materials in the environment pure and modified supercritical CO2 - T. R. Bilalov; F. M. Gumerov (Известия высших учебных заведений: Проблемы энергетики)
The results of experimental studies of solubility of TNT in pure and modified supercritical carbon dioxide (SC-CO2) are presented. Studies were carried out in a temperature range of 308.15-333.15 K and pressure interval 10.0-35.0 MPa on circulating type supercritical fluid extraction plant, R-401 produced by "Reaction Engineering Ink. " (South Korea). Experimental solubility data was described using the Peng-Robinson equation of state. The results of SC-CO2 - extraction of TNT from samples of hard burning materials and the efficiency of this process are shown.